1987
DOI: 10.1016/s0022-5347(17)43235-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Value of Ultrasonography, Computerized Tomography, Angiography and Excretory Urography in the Staging of Renal Cell Carcinoma

Abstract: From 1982 to 1985, 225 patients with renal cell carcinoma were treated by nephrectomy. To evaluate the diagnostic significance of ultrasonography in predicting tumor stage the results of ultrasonography, computerized tomography, renal angiography and excretory urography were compared to the histopathological findings. Since local tumor extension has a considerable impact on the operation strategy evaluation of the T classification was of particular interest. All 4 diagnostic procedures were performed in 73 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 11 publications
0
9
1
2
Order By: Relevance
“…In our study we evaluated the abil ity of MRI, along with CT and renal selective angiogra phy, to predict preoperatively not only the T stage of tumors but the N and V stages as well. Our overall cor rect T staging with CT was 64%, which was lower than the figures between 72.6 and 91 % reported in the inter national literature with 1 patient overstaged more than one stage (pT2 to T4) [4,6,13,18,19]. With MRI our overall success was with 63 % similar to that of CT. How ever, in the T3 stage, MRI had a remarkable sensitivity of 93%.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In our study we evaluated the abil ity of MRI, along with CT and renal selective angiogra phy, to predict preoperatively not only the T stage of tumors but the N and V stages as well. Our overall cor rect T staging with CT was 64%, which was lower than the figures between 72.6 and 91 % reported in the inter national literature with 1 patient overstaged more than one stage (pT2 to T4) [4,6,13,18,19]. With MRI our overall success was with 63 % similar to that of CT. How ever, in the T3 stage, MRI had a remarkable sensitivity of 93%.…”
Section: Discussioncontrasting
confidence: 49%
“…The contribution of excretory intravenous urog raphy, ultrasonography (US) and computerized tomog raphy (CT) in staging preoperatively renal cell carci noma is well documented [1][2][3][4][5][6]. Angiography has also been used extensively not only for evaluating venous involvement but for the T staging of tumors as well [5][6][7][8][9][10][11], However, a complete and more precise TNM preop erative staging, including evaluation of the renal vein, requires a combination of the above-mentioned diagnos tic methods [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preoperative diagnosis with reference to staging, CT has a high value. Tammela et al [22] and Frohmüller et al [23] found a correct local tumor staging in 80 and 72.3%, respectively. Also sonography has with 74.5 and 77.8% a high diagnostic ranking concerning tumor staging.…”
Section: Discussionmentioning
confidence: 94%
“…According to Taylor et al [7], CT is better than ultrasonography for detecting ACDK in long term dialysis patients, and CT has some margin of superi ority over ultrasonography in detecting small solid renal masses as well. However, Frohmiiller et al [ 15] suggested that ultrasonography appears to be more effective in the evaluation of the T stage of renal tumors compared to CT. No cystic neoplasms were mistaken for benign cysts by ultrasonography [16]. Our results confirm that ultraso nography is an effective method for the detection of renal cancer in patients on dialysis therapy.…”
Section: Discussionmentioning
confidence: 99%